Case Study of Speech Sound Disorder (SSD) in A 3 Year Old Child - Alfatih, M. Afief; Oktaviana, Mimbar; Putri, Ellyana Ilsan Eka (Procedia of Social Sciences and Humanities, 2024)
The aim of this research is to thoroughly understand cases of speech sound disorder that occur in children aged 3 years. The subjects in this study were children aged 3 years who had been diagnosed with speech sound disorder (SSD) and did not have neurological disorders or other developmental disorders. This research is qualitative research using a case study approach. Direct observation and interviews are used to collect research data which will then be analyzed using thematic analysis techniques. The results of this study show that the speech sound disorder (SSD) experienced by the subject occurred due to many factors starting from when she was still in the womb, the mother's mental health during pregnancy, as well as a lack of stimulus and interaction with the family. The use of gadgets as an alternative when children experience emotional problems or tantrums is also the cause of speech sound disorder (SSD) in children. It is hoped that consistent provision of therapies such as Play Therapy and Core Vocabulary Therapy will be able to help increase the amount of vocabulary in children with speech sound disorder (SSD).